1978
DOI: 10.1063/1.325311
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal reflection of electromagnetic waves from magnetized ferrite

Abstract: The reflection of a uniform plane wave from a ferrite magnetized normal to the plane of incidence has been investigated. The conditions for the occurrence of ordinary and total reflection from a lossless planar ferrite have been tabulated for all possible combinations of the relevant parameters. The phase shift on total reflection from a lossless ferrite is found to be nonreciprocal and magnetically tunable. The absorption of electromagnetic power on reflection from a lossy ferrite is also nonreciprocal. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In Ref. [19], different cases of reflection of electromagnetic waves from a ferrite-dielectric interface were studied. It was shown that in a certain range of the material parameters, a frequency region, and a region of a bias magnetic field, the phase shift on total reflection of electromagnetic waves from a lossless ferrite is nonreciprocal and magnetically tunable.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [19], different cases of reflection of electromagnetic waves from a ferrite-dielectric interface were studied. It was shown that in a certain range of the material parameters, a frequency region, and a region of a bias magnetic field, the phase shift on total reflection of electromagnetic waves from a lossless ferrite is nonreciprocal and magnetically tunable.…”
Section: Introductionmentioning
confidence: 99%